PENYUSUNAN MODEL PENINGKATAN STANDAR KINERJA ORGANISASI MENGGUNAKAN STRATEGI PROSPEKTOR DAN BUDAYA ORGANISASI ATHENA BAGI KOPERASI - Pramesti, Hernawati; Dananti, Kristyana (PRESTASI, 2013)
ABSTRACT Today the cooperative has undergone many developments and even competition. For the cooperativeis required to further improve its performance in serving the public. One effort that can be done is by the application of prospector strategy and organizational cultureof Athens, which is already known to positively influence the implementation of the organizations performance. The purpose of this study is to constructa model with improved performance incooperative prospector strategy implementation and organizational culture Athena. The first stage is to identify the existence ofthe cooperative. After the social construction obtained will then be compiled Cooperative performance improvement model that can be used to measure or evaluate the condition of acooperative as well as the development of performance standards, which will ultimately benefit the improvement of organizational performance and national development in general. The approach used is qualitative-phenomenological approach for implementers to test the model. The unitof analysis is cooperative in Surakarta. The units of analisys are the organizers, participants and facilities as sociated with the organization. Participants performed retrieval based on the criteria of successin generating financial report sorganizers. The analisys is descriptive qualitative method. The out put of this research is a model of social rekasaya a cooperative organization performance improvement. Â Keywords: Performance Organization, Cooperation, and prospector strategy and organizational cultureof Athens